Konsep Mahar Dalam Pandangan Mayarakat Kota Subulussalam (Studi Kasus Di Kecamatan Simpang Kiri) - Medi Ardiansyah, Efnedy Arief, Sulaiman Tamba (Taushiah: Jurnal Hukum, Pendidikan dan Kemasyarakatan, 2021)
Dowry is a mandatory gift from a prospective husband to a prospective wife as a form of application of syar'i orders. The determination of the dowry in Islam is not determined by the amount and form. However, this is different from the practice carried out by the people of Tangga Besi Village, Simpang Kiri District, Subulussalam City, which determines the amount of dowry. The purpose of this study is to find out the dowry in community marriages and the reasons for youth to marry or not in Tangga Besi Village, Simpang Kiri District, Subulussam City. The subjects in the study were 16 people, namely the head of the local KUA, religious leaders, traditional leaders, village heads and the community, 5 youths, and 6 women and one parent. To answer these problems using the type of research field research (field), with a qualitative approach. Data collection techniques were carried out by means of interviews, observation and documentation. The results showed that the determination of the dowry in the marriage of the Simpang Kiri District, Subulussalam City had a negative influence, where men and women were hampered in getting married, on average some men and women over the age of 35 years and over were newly married. With the increasing number of dowries, the number of marriages is decreasing, some men prefer not to marry. Those who determine the dowry in marriage are carried out by the family/parents and themselves. Determination of the amount of dowry in terms of descent, beauty, level of education and living at the bride's house, these are factors that stand out from the high dowry in Simpang Kiri District, Subulussalam City. The reasons for youth to marry and not marry in (1) are caused by the fact that young people are still overseas, (2) because there is no permanent job yet. (3) caused by the high amount of dowry.